Exploring feminist urban geographies: women workers in the peanut industry of Osmaniye, Türkiye - Sezen Savran Penbecioğlu; Kadriye Burcu Yavuz (ESTOA: Revista de la Facultad de Arquitectura y Urbanismo de la Universidad de Cuenca)
Osmaniye is well-known for its substantial peanut production, and women workers play a crucial role in every aspect of this sector. The article manifests original research findings on the working conditions and the socio-spatial experiences of women workers, who are integral to the peanut industry. The findings rely on semi-structured in-depth interviews and non-participant observations conducted in 2022, involving women workers and other key actors at two major factories. Among the common issues confronted by women workers are low wages, precarious working conditions, and unsuitable work environments and worsening mobility patterns which exacerbate their urban daily life experience. Their work does not lead to empowerment or an increased usage of space but instead results in a “double shift”; and a negative perception of their work. Ultimately, the working environment and the daily urban geographies of women workers dramatically reproduces patriarchal dynamics.